Dynamic response and fracture analysis of basalt fiber reinforced plastics and aluminum alloys adhesive joints. (15th July 2021) - Wang, Shaoluo; Wang, Shuhao; Li, Guangyao; Cui, Junjia
Highlights: Effects of loading rates on mechanical properties and failure behaviors of basalt fiber reinforced plastics and aluminum alloys single-lap adhesive joints were investigated. Failure process and strain evolution of the adhesive joints were recorded and analyzed via high speed camera and digital image correlation (DIC) technique. Micromorphology of fracture surface was observed by SEM, and failure mechanisms were discussed. Corresponding relations between the loading rates and the change of failure mode and stress distribution were revealed. Abstract: Recently, the use of environmentally friendly natural fibers as reinforcement materials has attracted much attention to achieve lightweight structures. Basalt fiber reinforced plastic (BFRP) was widely used as an alternative material with low price and excellent performance. In this study, the effects of loading rates and different material properties on mechanical properties and fracture behavior of BFRP and aluminum (Al) single-lap adhesive joints were investigated. The fracture processes and strain evolution were recorded and analyzed by high speed camera and digital image correlation (DIC) technique. The microscopic appearance of fracture surface was also investigated to explore the effects of loading rates and material types on the failure modes. Results showed that all specimens were sensitive to loading rates. The average peak load increased by 50% at the speed of 5 m/s compared with quasi-static condition of 2 mm/min and BFRP/BFRP joints had higher strength than BFRP/Al joints. The stiffness of adherends influenced the failure behavior of the joints. Adhesive failure occurred at the edge of the substrate with large plastic deformation and the ratio decreased with the loading rates increasing. Fiber tear occurred in all BFRP adherends because of the increase in loading speed and the poor bonding between basalt fibers and matrix. Meanwhile, there was a corresponding relationship between the loading rates and the change of failure mode and stress distribution.